Extracellular vesicles as actors in the air pollution related cardiopulmonary diseases. (27th May 2020) - Alkoussa, Stéphanie; Hulo, Sébastien; Courcot, Dominique; Billet, Sylvain; Martin, Perrine J.
Abstract: Many associations were reported between air pollution and daily mortality rates for cardiopulmonary diseases. Humans are exposed to a mixture of oxidizing gases and particles, both anthropogenic and natural. Exposure to air toxics causes or exacerbates cardiovascular damages and respiratory diseases. Numerous studies have identified the induction of oxidative stress and sustained inflammatory response as among the main known underlying pathophysiological mechanisms of air pollutants. More recently, the relationship between these mechanisms of action and the secretion of extracellular vesicles (EVs) by lung cells has been revealed. EVs have been shown to be important mediators of cellular communication in the body. The purpose of this review is to first recall the main air pollutants. Then, the cardiopulmonary diseases caused by exposure to air pollution and the pathophysiological mechanisms are presented before showing, through an exhaustive review of the literature, the involvement of EVs in the toxicity of air pollutants and the initiation of cardiopulmonary diseases.